Sensorimotor Relationalism and Conscious Vision. Issue 1 (22nd May 2022) - Ward, Dave
Abstract: I argue that the phenomenal properties of conscious visual experiences are properties of the mind-independent objects to which the subject is perceptually related, mediated by the subject's practical understanding of their sensorimotor relation to those properties. This position conjoins two existing strategies for explaining the phenomenal character of perceptual experiences: accounts appealing to perceivers' limited, non-inferential access to the details of their sensory relation to the environment, and the relationalist conception of phenomenal properties. Bringing these two positions together by emphasizing their sensorimotor common ground allows each one to respond to damaging objections using the resources of the other. The resulting 'sensorimotor relationalism' about conscious vision provides a promising schema for explaining phenomenal properties of perceptual states, replacing 'Hard' questions with tractable ones about the perceptual relation and its sensorimotor underpinnings.